2016
DOI: 10.1371/journal.pone.0155918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Brown Rice Based Vegan Diet and Conventional Diabetic Diet on Glycemic Control of Patients with Type 2 Diabetes: A 12-Week Randomized Clinical Trial

Abstract: ObjectiveSeveral intervention studies have suggested that vegetarian or vegan diets have clinical benefits, particularly in terms of glycemic control, in patients with type 2 diabetes (T2D); however, no randomized controlled trial has been conducted in Asians who more commonly depend on plant-based foods, as compared to Western populations. Here, we aimed to compare the effect of a vegan diet and conventional diabetic diet on glycemic control among Korean individuals.Materials and MethodsParticipants diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(224 citation statements)
references
References 27 publications
1
197
2
5
Order By: Relevance
“…More recent studies published after the release of this meta‐analysis revealed comparable results. In 2016, Lee et al reported the effects of a brown rice‐based vegan diet on glycemic control in patients suffering from T2D and noted a statistically significant HbA1c reduction of −0.9% in participants with high compliance . In 2017, Ramal and colleagues paired a plant‐based diet low in fat and high in fiber with lifestyle support in the treatment of Latinos with T2D who live in medically underserved areas .…”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
“…More recent studies published after the release of this meta‐analysis revealed comparable results. In 2016, Lee et al reported the effects of a brown rice‐based vegan diet on glycemic control in patients suffering from T2D and noted a statistically significant HbA1c reduction of −0.9% in participants with high compliance . In 2017, Ramal and colleagues paired a plant‐based diet low in fat and high in fiber with lifestyle support in the treatment of Latinos with T2D who live in medically underserved areas .…”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
“…7 When 50 g of WR, corresponding to one-third of the daily intake, is replaced by BR, the risk of developing type 2 diabetes is reduced by 16%. 8 However, it may be difficult for people to continue eating BR on a daily basis due to its taste and texture, even though BR could prevent or improve diabetes compared with WR.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the follow‐up to the 2006 RCT by Barnard et al, which tested an energy‐controlled diet compared to an ad libitum vegan diet and initially found within‐group but not between‐group advantages for both diets, found a substantial decline in benefits occurring between 22 and 74 weeks; however, when the data were analysed before medication changes, a significant between‐group reduction in HbA1c was observed in the vegan group . In a review by Rinaldi et al whose conclusions favoured plant‐based diets, six trials did not consistently show improvements in glycaemic control, weight loss or CVD risk factors . The ADA also cited a commentary based on a non‐systematic review, a cross‐sectional study, and an assessment of diets in Barnard et al 2006.…”
Section: Resultsmentioning
confidence: 99%
“…We identified nine studies not included in the ADA review, three of which were published after the 2018 standards (Table S4). Three RCTs found reductions in HbA1c from baseline, and two found the test diet superior compared to the control diet . In these studies, the plant‐based diets were compared to an energy‐restricted diet, the recommended Korean Diabetes Association diet, and the participants' usual diet.…”
Section: Resultsmentioning
confidence: 99%